The number of CAG and GGN triplet repeats in the Androgen Receptor gene exert combinatorial effect on hormonal and sperm parameters in young men. (23rd March 2017) - Grigorova, M.; Punab, M.; Kahre, T.; Ivandi, M.; Tõnisson, N.; Poolamets, O.; Vihljajev, V.; Žilaitienė, B.; Erenpreiss, J.; Matulevičius, V.; Laan, M.
Summary: Androgen receptor (AR) is a transcription factor that is activated upon binding to testosterone (T) and is implicated in regulating the expression of reproduction‐related genes. The human AR gene (Xq11‐12) spans 186, 588 bp and eight exons. N‐terminal transactivation domain of the encoded AR protein harbours two polymorphic stretches of identical amino acids, a polyglutamine tract (encoded by 8‐37 CAG‐repeats) and a polyglycine tract (encoded by 10‐30 GGN‐repeats). We set forward to analyse independent and combinatory effects of the length of these repetitive tracts on male reproductive hormones, testicular and sperm parameters in a population‐based cohort of Baltic young men ( n  = 974; aged 20.1 ± 2.1 years). We designed an assay to amplify and detect simultaneously the variants of both polymorphic repeats. The study revealed that elongated AR CAG tract was associated with lower FSH (linear regression: p  =   0.0002, effect per repeat −0.056 IU/L). As a novel finding, the carriers of GGN‐stretch with ≥24 repeats showed a trend for decreased sperm concentration ( p  =   0.027). Although neither of the variants exhibited an isolated effect on circulating T, their allelic combinations modulated serum T levels, as well as sperm concentration. The lowest T was measured for men carrying the AR gene with long CAG ( n  ≥ 25) and short GGN ( n  ≤ 21) repeat tracts (mean 18.8 vs. 25.5–28.6 nmol/L for the other AR variants, p  =   0.017). The lowest sperm concentration was detected among individuals with both elongated repetitive stretches (CAG, n  ≥ 25 and GGN, n  ≥ 24; mean 49.0 vs. 68.4–72.1 mill/mL for the other variants; p  =   0.00059). The innovative study design enabled to clearly demonstrate a combinatory impact of CAG and GGN repeat lengths at male reproductive parameters. As AR regulates transcription of over 900 genes in many tissues and organs, the combinatory effects of these common repeat‐length variants on male physiology in the wider context and across lifetime are still to be assessed.